1988
DOI: 10.1901/jeab.1988.49-21
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent‐schedule Performance: Effects of Relative and Overall Reinforcer Rate

Abstract: Six pigeons were trained to respond on two keys, each of which provided reinforcers on an arithmetic variable-interval schedule. These concurrent schedules ran nonindependently with a 2-s changeover delay. Six sets of conditions were conducted. Within each set of conditions the ratio of reinforcers available on the two alternatives was varied, but the arranged overall reinforcer rate remained constant. Each set of conditions used a different overall reinforcer rate, ranging from 0.22 reinforcers per minute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
112
6

Year Published

1988
1988
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 22 publications
27
112
6
Order By: Relevance
“…When the overall reinforcer rate was increased in Condition 2, higher values of sensitivity to reinforcement were obtained in both groups. This increase is the established result, both in steady-state concurrent-schedule procedures (Alsop & Elliffe, 1988;Elliffe & Alsop, 1996) and in the frequently changing procedure used in the present study (Davison & Baum, 2000). However, when the overall reinforcer rate was decreased to the lowest value tested in Condition 3, sensitivity to reinforcement values decreased, but not below the Condition 1 levels.…”
Section: Discussionsupporting
confidence: 70%
“…When the overall reinforcer rate was increased in Condition 2, higher values of sensitivity to reinforcement were obtained in both groups. This increase is the established result, both in steady-state concurrent-schedule procedures (Alsop & Elliffe, 1988;Elliffe & Alsop, 1996) and in the frequently changing procedure used in the present study (Davison & Baum, 2000). However, when the overall reinforcer rate was decreased to the lowest value tested in Condition 3, sensitivity to reinforcement values decreased, but not below the Condition 1 levels.…”
Section: Discussionsupporting
confidence: 70%
“…First, Alsop and Elliffe (1988) showed that sensitivity to variations in relative reinforcement increases with increases in overall rates of reinforcement. Given the lower overall accuracies with the shorter sample duration in the present experiment, one Bias (log b) 9 3 6 9 5 6 1 4 4 2 3 2 9 6 6 9 5 7 1 1 5 8 2 2 2 9 3 6 9 5 6 1 4 4 2 3 2 9 6 6 9 5 7 1 1 5 8 2 2 2…”
Section: Discussionmentioning
confidence: 99%
“…Relatively greater values ofSAlSD are thus associated with more self-control and vice versa. Note that the generalized matching law is being used here simply as a scaling method, independently ofits validity as a general model of choice (Alsop & Elliffe, 1988;Logue, Forzano, & Tobin, 1992;McCarthy, 1991).…”
Section: (2)mentioning
confidence: 99%